MDA effects on morphophysiology and reproduction of Daphnia magna – preliminary data - Morão, A. M.; Carvalho, A. R.; Couto, C.; Carrola, J. S.; Costa, P.; Castro, B.; Tiritan, M. E.; Ribeiro, C. (Scientific Letters, 2023)
Background: Psychoactive substances and their metabolites are considered emergent contaminants, raising environmental concerns due to the continuous input into aquatic ecosystems [1]. MDA (3,4-methylenedioxyamphetamine) is a pharmacologically active substance that represents the major metabolite of 3,4-methylenedioxymethamphetamine (MDMA); MDA may be present in MDMA preparations or occur as an illegal psychoactive substance [2]. Considering the possible implementation of MDMA-assisted psychotherapy along with the increased recreational interest in MDA, the presence of MDA in aquatic ecosystems is expected to increase as well as its effects on non-target organisms, including invertebrates [1,3]. Since the ecotoxicological impact of MDA remains unknown, studying its toxic effects on an environmentally relevant organism is most important. Objective: This work aimed to assess the effects of possible MDA-induced toxicity on Daphnia magna through the evaluation of morphophysiological and reproductive endpoints. Methods: Neonates (<24 hours) were exposed to three concentrations of MDA (0.1, 1 and 10 mg/L) for 9 days. Exposures and control were performed with 5 replicates with 20 organisms each. On days 3 and 9, morphophysiological endpoints (body size, heart size and area, and heart rate) and reproductive endpoints (number of ovigerous daphnia and fertility) were determined. In parallel, a standard 21-d reproduction assay was conducted (MDA concentrations: 0, 0.10, 0.18, 0.32, 0.56, 1.00, 1.79 mg/L). Results: Morphophysiological endpoints increased with MDA concentration on the third and ninth day of exposure. An increase in the number of ovigerous daphnia and fecundity was found at 10 mg/L of MDA. In the 21-d assay, MDA caused a significant reduction in fecundity, body size and rate of increase from 0.18 mg/L upwards. Conclusions: Data are suggestive of some adverse influence of MDA on the analyzed endpoints. Nevertheless, other toxicity biomarkers should be evaluated to obtain insight on a mechanistic explanation for the observed effects.